BIM : a methodology to transform business processes into software systems - Duarte, Francisco J. (2012)
This manuscript proposes a guiding methodology to obtain a software system that supports the execution of the business processes existing within an organization. The methodology promotes the usage of business process reference models and intends to reduce the implementation time of the software systems. The methodology assumes four distinct phases and several abstraction levels and is applicable both when developing systems from scratch or in re-engineering contexts. The methodology embodies a special phase to handle the diversity of the business processes of an organization. By tailoring process reference models and by considering the characteristics of a specific organization, a proper set of business processes is derived for that organization. Then, we can obtain a suitable information system and implement its automatable parts in a software solution that can run on top of open source software frameworks. We also present four new supporting concepts to the methodology, and a summarized execution of it.